Strategi Komunikasi Pembangunan Masyarakat - Iwan Armawan (Khidmatussifa: Journal of Islamic Studies, 2022)
The development strategy determines the communication strategy, so the meaning of development communication also depends on the capital or development paradigm chosen. Development is a process whose emphasis is on harmony between aspects of outward progress and inner satisfaction. When viewed in terms of communication science which also studies the problem of the process, namely the process of delivering one's message to others to change attitudes, opinions and behavior. So development basically involves at least three components, namely development communicators (either government officials or the community), development messages containing development ideas or programs and development communicators, namely the wider community of development targets. The development of Indonesian society is pragmatic, namely a pattern that generates innovation for the present and the future. The communication function is at the forefront of changing attitudes and behavior of Indonesian people as the main actors of development, both as subjects and as objects of development. Keywords: communication strategy, development communication